A film, preparation method and application thereof

Through the solvent-free method, the active material and the conductive material are mixed and heated and deposited organic polymer materials, the existing film preparation technology is solved, the problems of complex, high energy consumption and heavy pollution are achieved, and the film is improved. The adhesion and density reduce energy consumption.

CN115763708BActive Publication Date: 2025-01-03TIANJIN PLANNANO ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211354914.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-01
Publication Date
2025-01-03
Estimated Expiration
2042-11-01

AI Technical Summary

Technical Problem

The existing film preparation technology has problems such as complex process, high energy consumption and heavy pollution, especially in the wet process, which requires a large amount of organic solvent and high-temperature heating, resulting in complex and unenvironmental protection.

Method used

By using the solvent-free method, by mixing the active material and the conductive material, heating it and depositing organic polymer material on the current collector, forming a thin film by rolling pressure, simplifying the process flow, avoiding the use of the separator, and achieving green and efficient film preparation.

Benefits of technology

The film preparation is achieved with simplicity, efficiency, low cost and low pollution, which improves the adhesion, density and life of the film, reduces energy consumption, and eliminates the need for flammable and explosive organic solvents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115763708B_ABST
    Figure CN115763708B_ABST
Patent Text Reader

Abstract

The present invention relates to a film, a preparation method and its application, and relates to the field of new energy devices and energy storage, and comprises the following steps: step S1, mixing: fully mixing active materials and conductive materials to obtain a mixture of active materials / conductive materials; step S2, transferring: transferring the mixture obtained in step S1 to a current collector to obtain a current collector covered with active materials / conductive materials; step S3, depositing: depositing a layer of organic polymer material on the fluid obtained in step S2 to obtain an intermediate film on the current collector; step S4, heating and rolling: heating the intermediate film obtained in step S3, and then rolling to obtain a film on the current collector for energy storage devices. A green, efficient, pollution-free, solvent-free and simple-to-operate film preparation method is provided, which can be obtained by simply mixing and heating the required materials, and the obtained film assembly does not require a diaphragm, and the compaction density and life are more excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy devices and energy storage, and in particular to a thin film, a preparation method and application thereof. Background Art

[0002] Thin films are widely used in energy storage devices, including positive electrodes, negative electrodes, and separators. Simple, efficient, and energy-saving thin film preparation technology is crucial for high-performance energy storage devices. At present, most electrochemical device manufacturers at home and abroad use wet and dry methods to prepare thin films for energy storage devices.

[0003] The traditional wet-process thin film preparation process has the disadvantages of complex process, high energy consumption and environmental pollution. As for the positive and negative electrodes, the preparation process includes slurry, coating, rolling and other process flows. The slurry step is to stir and disperse the active material, conductive agent and binder in a large amount of organic solvent for a long time to obtain a slurry that meets the process requirements; and the coating step is to evenly coat the slurry on the current collector, and then heat it at high temperature, blow air to remove the solvent, and finally roll it to obtain the pole piece. It can be seen that the preparation process of the traditional wet-process pole piece is time-consuming, energy-intensive and polluting. The preparation of the diaphragm has similar disadvantages. The wet-process diaphragm process mixes liquid hydrocarbons or some small molecular substances with polyolefin resins, heats and melts them to form a uniform mixture, then cools them for phase separation, presses them to obtain a membrane, and then heats the membrane to a temperature close to the melting point, performs biaxial stretching to orient the molecular chains, and then uses a volatile solvent to extract the plasticizer from the film, thereby obtaining a mutually interpenetrating submicron-sized microporous membrane material.

[0004] The thin film for energy storage devices formed by dry method has good electrochemical properties due to the absence of impurities. The dry method is to mix the active material, conductive agent and binder to form an average melt, form a lamellar structure under tensile stress during extrusion, heat to obtain a hard elastic polymer film, and finally stretch it at a certain temperature to form slit-shaped micropores, and obtain a microporous membrane after heat setting. For example, patent CN102629681A discloses a powder-based electrode forming method, using powder active material, powder conductive agent and powder binder to be uniformly mixed by a three-dimensional powder mixer or a gravity-free powder mixer, and then crushed by a low-temperature pulverizer, and then extruded by a twin-screw extruder or an internal mixer / open mill, and then hot-pressed by a calender to reach the target thickness, and finally composited with a three-layer current collector of printed conductive glue to form an electrode and cold rolled to increase the compaction density. Patent CN102723211A discloses a high-performance supercapacitor and its manufacturing process, which uses a three-dimensional mixer or a weightless mixer for dry powder mixing to ensure that different components are evenly distributed, and no water or solvent is introduced during the production of positive and negative electrodes, thereby ensuring the purity of the electrode material to the greatest extent. Although the solvent-assisted processing method is abandoned, thereby ensuring the purity of the electrode material to the greatest extent, the three-layer composite with the current collector of the printed conductive glue after the film is prepared has the problem of re-adhesion and the need for a separate diaphragm.

[0005] In view of this, the present invention has developed a thin film preparation technology with better performance, which is efficient, green and energy-saving, and is crucial to new and high-performance energy storage technology. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a film, a preparation method and its application. The purpose is to overcome the shortcomings of the existing film preparation technology, namely, the preparation process is complicated and lengthy, requires a large amount of organic solvents, is energy-intensive, highly polluting, and complicated to operate, and to provide a green, efficient, pollution-free solvent-free method with simple operation for preparing films, which can be prepared by simply mixing and heating the required materials, and the film assembly does not require a diaphragm, and has better compaction density and lifespan.

[0007] In order to solve the above technical problems, the first object of the present invention is to provide a method for preparing a thin film, comprising the following steps:

[0008] Step S1, mixing: fully mixing the active material and the conductive material, wherein the weight ratio of the active material to the conductive material is (80-100): (0.1-20), to obtain a mixture of active material / conductive material;

[0009] Step S2, transfer: transferring the mixture of active material / conductive material obtained in step S1 to a current collector to obtain a current collector covered with active material / conductive material;

[0010] Step S3, deposition: depositing a layer of organic polymer material on the current collector covered with the active material / conductive material obtained in step S2 to obtain an intermediate film on the current collector;

[0011] Step S4, heating and rolling: the intermediate film obtained in step S3 is heated, the organic polymer material melts and fills the gaps between the active material and the conductive material to reach the surface of the current collector, and then rolled to obtain a thin film on the current collector for the energy storage device.

[0012] The beneficial effects of the present invention are as follows: the preparation method adopted by the present invention is simple, efficient, pollution-free, low-cost and can be produced on a large scale and continuously; the thin film preparation technology does not require the use of flammable and explosive organic solvents, and is more green, safe and energy-saving. The preparation method adopted overcomes the defects of the existing thin film preparation technology of high pollution, high energy consumption and complex process flow.

[0013] After the temperature increase treatment in step S4 of the present invention, the organic polymer material melts and fills the gaps between the active material and the conductive material mixture to reach the current collector, thereby not only tightly adhering the two together, but also increasing the adhesion between the coating layer and the current collector; further, the organic polymer material on the surface of the coating layer also forms a thin film, which acts as a diaphragm, so the thin film prepared by the present invention no longer needs to use a commercial diaphragm to assemble the energy storage device, which is low-cost and simpler in process; the thin film prepared by the present invention can obtain an energy storage device product with higher adhesion, greater coating surface density, and higher compaction density.

[0014] Based on the above technical solution, the present invention can also be improved as follows.

[0015] Furthermore, the active material described in step S1 includes but is not limited to a positive electrode material or a negative electrode material used in a lithium-ion battery, or a positive electrode material or a negative electrode material used in a supercapacitor.

[0016] Furthermore, the active material described in step S1 includes one or a mixture of two or more of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, ternary materials, graphite, hard carbon, silicon carbon materials, and activated carbon; the conductive material includes but is not limited to one or a mixture of two or more of nanotubes, graphene, and conductive carbon black.

[0017] Furthermore, the mixing method described in step S1 is one or a combination of two or more of mechanical stirring, ball milling, and air flow milling.

[0018] The beneficial effect of adopting the above further scheme is: through the above mixing method, the active material and the conductive agent are fully mixed, the ineffective gaps are reduced, the contact resistance is reduced, the compaction density is increased, thereby increasing the area / volume specific capacity and improving the power density. Further, the current collector described in step S2 includes copper foil, aluminum foil, carbon-coated copper foil, carbon-coated aluminum foil or carbon paper.

[0019] Furthermore, the transfer method described in step S2 includes one or more of scraping, spraying, and spin coating; the organic polymer material deposition method described in step S3 includes one or more of scraping, spraying, chemical vapor deposition, and plasma enhanced vapor deposition.

[0020] The beneficial effect of adopting the above further scheme is: through the above operation, the mixture of active material / conductive material can be efficiently and evenly coated on the surface of the substrate, and the organic polymer material is more closely combined with the mixture of active material / conductive material, thereby reducing the contact resistance and increasing the surface density, thereby achieving high energy density and high power performance of the energy storage device.

[0021] Furthermore, the organic polymer material described in step S3 includes, but is not limited to, one or a mixture of two or more of polyvinylidene fluoride, polyethylene, polypropylene, sodium carboxymethyl cellulose, polyvinyl alcohol, polyethylene oxide, and polytetrafluoroethylene.

[0022] Furthermore, the heating treatment method described in step S4 includes one or more of direct heating, ultraviolet irradiation, infrared irradiation, and microwave heating. The heating temperature is 80-500 degrees.

[0023] The beneficial effect of adopting the above further scheme is that at a temperature of 80-500 degrees, after the organic polymer material is treated, the active material / conductive material mixture can be adhered to the current collector, and the surface organic polymer material plays the role of a separator.

[0024] The second object is to provide a film prepared by the film preparation method as described above.

[0025] The beneficial effect of adopting the above scheme is that the thin film prepared by the present invention no longer needs to use commercial diaphragms to assemble energy storage devices, which is low-cost and simpler in process.

[0026] The third object is to provide an energy storage device, which includes a positive electrode, a negative electrode and a separator, and is made by using the above-mentioned thin film as the positive electrode, or / and the negative electrode, or / and the separator.

[0027] The beneficial effect of adopting the above scheme is that the film prepared by the present invention can obtain an energy storage device product with higher adhesion, greater coating surface density and higher compaction density. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a diagram of a negative electrode sheet with a coating prepared in Example 1 of the present invention;

[0029] Figure 2 The negative electrode and coating after the coating of the negative electrode plate is separated in Example 1 of the present invention, wherein the left picture is the negative electrode plate after the coating is separated, and the right picture is the white coating;

[0030] Figure 3 This is a comparison diagram of the bonding strength of the negative electrode sheet prepared by Example 1 of the present invention, and the electrode sheet prepared by the wet method and the electrode sheet prepared by the existing dry method;

[0031] Figure 4 This is a comparison chart of the lifespan of the dry-process supercapacitor, the wet-process supercapacitor DC and the supercapacitor prepared by the existing dry process in the present invention;

[0032] Figure 5 The increase rate of internal resistance of the dry-process supercapacitor and the wet-process supercapacitor prepared by the existing dry process is compared in the present invention. DETAILED DESCRIPTION

[0033] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0034] Example 1

[0035] A method for preparing a thin film electrode for a lithium ion battery comprises the following steps:

[0036] Step S1: stirring and mixing natural graphite and conductive carbon black at a mass ratio of 98:2 for 3 hours, and then spraying the mixture onto the surface of the copper foil to obtain a copper foil covered with the mixture of natural graphite and conductive carbon black;

[0037] Step S2: on the basis of step S1, spraying polyvinylidene fluoride powder to obtain polyvinylidene fluoride / (natural graphite and conductive carbon black mixture) / copper foil;

[0038] Step S3: The intermediate product obtained in step S2 is heated to about 200 degrees, so that the polyvinylidene fluoride melts and passes through the gap between the natural graphite and the conductive carbon black mixture, adheres the coating layer, and acts as a separator to obtain a negative electrode. Figure 1 ;

[0039] Step S4: Perform the same operation as steps S1-S3 to prepare a positive electrode made of lithium iron phosphate positive electrode material based on carbon-coated aluminum foil, and use the two as electrodes without a separator to assemble a lithium-ion battery.

[0040] pass Figure 1 and Figure 2It can be seen that the surface of the battery pole piece prepared by the method of the present invention has a polymer coating, and no additional diaphragm material is required in the process of assembling lithium-ion batteries. Figure 3 It can be seen that the bonding strength of the battery pole piece prepared using the method of the present invention is significantly better than that of the wet-process pole piece, and the bonding strength is increased by about 40%; the bonding strength of the battery pole piece prepared using the method of the present invention is also better than the existing dry-process pole piece, and the bonding strength is increased by about 12.5%.

[0041] In addition, the wet electrode preparation steps are as follows:

[0042] 1. First, dissolve the binder into the organic solvent by stirring for a long time, then add the active material and the conductive agent and continue to stir and mix evenly to prepare a slurry; 2. Transfer the slurry to the current collector by coating, and heat it in an oven to remove the organic solvent to obtain a semi-finished electrode;

[0043] 3. The semi-finished electrode piece is rolled to obtain the final electrode piece. The rest is the same as that of the first embodiment.

[0044] The existing dry-process electrode preparation steps are as follows:

[0045] 1. Dissolve the binder in the solvent, then add the conductive agent to prepare a coating slurry;

[0046] 2. Applying the slurry prepared in step 1 to the current collector and heating to remove the solvent to obtain a current collector coated with a conductive agent;

[0047] 3. Premix the active material and the conductive agent, then add the binder and mix further until uniform; then further mix the resulting mixture through a fiberization process;

[0048] 4. The mixture obtained in step 3 is prepared into a film by high temperature hot pressing;

[0049] 5. The film obtained in step 4 is hot pressed onto the current collector with coating prepared in step 2 to obtain the final electrode. The rest is the same as in Example 1.

[0050] Example 2

[0051] A method for preparing a thin film electrode of a supercapacitor comprises the following steps:

[0052] Step S1: mixing activated carbon and superconducting carbon black in a mass ratio of 95:5 by ball milling for 5 hours, and then spraying the mixture onto the surface of the carbon-coated aluminum foil to obtain an aluminum foil coated with a mixture of activated carbon and superconducting carbon black;

[0053] Step S2: on the basis of step S1, spraying polyvinyl alcohol powder to obtain a polyvinyl alcohol-covered (natural graphite and conductive carbon black mixture) / copper foil intermediate product;

[0054] Step S3: heating the intermediate product obtained in step S2 to about 250 degrees by infrared radiation, so that the polyvinyl alcohol melts and passes through the activated carbon and superconducting carbon black, adheres the coating layer, and acts as a diaphragm to obtain a supercapacitor electrode;

[0055] Step S4: Using the product obtained in step S3 as a supercapacitor electrode, assembling a supercapacitor.

[0056] Table 1 Supercapacitor electrode sheet prepared using Example 2, wet electrode sheet and existing dry electrode sheet

[0057] Compacted density comparison

[0058]

[0059] pass Figure 4-5 As shown in Table 1, the compaction of the supercapacitor electrode prepared by the method of the present invention is increased by about 20% compared with the wet electrode; the compaction of the supercapacitor electrode prepared by the method of the present invention is increased by about 13% compared with the existing dry electrode. Compared with the wet supercapacitor, the supercapacitor prepared by the method of the present invention has a significantly improved lifespan and a significantly reduced internal resistance increase rate. The capacity retention rate of the wet electrode is reduced to 80% after 1700 hours of circulation, and the internal resistance is increased to 160%, while the dry electrode of the present invention reaches the above values ​​after 2800 cycles; compared with the existing dry electrode supercapacitor, the supercapacitor prepared by the method of the present invention has a significantly improved lifespan of 4%, and a significantly reduced internal resistance increase rate of 10%.

[0060] Note: The preparation methods of the wet electrode in this embodiment 2 and the existing dry electrode are described in reference to the description of embodiment 1.

[0061] Example 3

[0062] A method for preparing a thin film electrode for a lithium ion battery comprises the following steps:

[0063] Step S1: Stir and mix the silicon-carbon negative electrode, Super P, and carbon nanotubes at a mass ratio of 98:1:1 for 4 hours, and then scrape and apply to the copper foil with a carbon layer on the surface to obtain a copper foil covered with a silicon-carbon negative electrode / Super P / carbon nanotube mixture;

[0064] Step S2: on the basis of step S1, polyethylene powder is sprayed to obtain polyethylene / (silicon-carbon negative electrode / SuperP / carbon nanotube mixture) / copper foil;

[0065] Step S3: heating the intermediate product obtained in step S2 to about 120 degrees, so that the polyethylene melts and passes through the gaps between the coating layer particles, adheres the coating layer, and acts as a diaphragm;

[0066] Step S4: The same operation is performed to prepare a lithium cobalt oxide positive electrode material based on carbon-coated aluminum foil, and the two are used as electrodes to assemble a lithium-ion battery.

[0067] Table 2 Battery pole pieces prepared using Example 3, wet pole pieces and existing dry pole pieces

[0068] Compacted density comparison

[0069]

[0070] It can be seen from Table 2 that the compaction density of the positive and negative electrode sheets of the battery prepared using Example 3 is significantly higher than that of the positive and negative electrode sheets of the battery prepared by the wet method; the compaction density of the positive and negative electrode sheets of the battery prepared using Example 3 is significantly higher than that of the positive and negative electrode sheets of the battery prepared by the existing dry method.

[0071] Note: The preparation methods of the wet electrode in this embodiment 3 and the existing dry electrode are described in reference to the description of embodiment 1.

[0072] Note: The pole pieces obtained in the above embodiments are used as positive and negative electrodes, and no diaphragm is used. The energy storage device is assembled by packaging, baking to remove moisture, and injecting liquid. The electrolyte uses a mixture of commercial ethylene carbonate (EC), propylene carbonate (PC) and dimethyl carbonate (DMC) (volume ratio of 1:1:1) as an organic solvent, and 2% vinylene carbonate (VC) additive. The electrochemical performance of the battery cell is tested.

[0073] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a thin film, characterized in that: The steps include: Step S1, mixing: fully mixing the active material and the conductive material, wherein the weight ratio of the active material to the conductive material is (80-100): (0.1-20), to obtain a mixture of the active material / conductive material; Step S2, transfer: transfer the mixture of active material / conductive material obtained in step S1 to a current collector to obtain a current collector covered with active material / conductive material; Step S3, deposition: depositing a layer of organic polymer material on the current collector covered with the active material / conductive material obtained in step S2 to obtain an intermediate film on the current collector; Step S4, heating and rolling: the intermediate film obtained in step S3 is subjected to a temperature treatment so that the organic polymer material is melted and fills the gap between the active material and the conductive material to reach the surface of the current collector, and then rolled to obtain a film on the current collector for the energy storage device; The active material / conductive material mixture transfer method described in step S2 includes one or more of the following: scraping, spraying, and spin coating; the organic polymer material deposition method described in step S3 includes one or more of the following: scraping, spraying, and spin coating; The organic polymer material described in step S3 includes one or a mixture of two or more of polyvinylidene fluoride, polyethylene, polypropylene, sodium carboxymethyl cellulose, polyvinyl alcohol, polyethylene oxide, and polytetrafluoroethylene.

2. The method for preparing a thin film according to claim 1, characterized in that: The active material described in step S1 includes a positive electrode material or a negative electrode material used in a lithium-ion battery, or a positive electrode material or a negative electrode material used in a supercapacitor.

3. The method for preparing a thin film according to claim 2, characterized in that: The active material described in step S1 includes one or a mixture of two or more of lithium iron phosphate, lithium manganese oxide, lithium cobalt oxide, ternary materials, graphite, hard carbon, silicon carbon materials, and activated carbon; the conductive material includes one or a mixture of two or more of nanotubes, graphene, and conductive carbon black.

4. The method for preparing a thin film according to claim 1, characterized in that: The mixing method described in step S1 is one or a combination of two or more of mechanical stirring, ball milling, and air flow milling.

5. The method for preparing a thin film according to claim 1, characterized in that: The current collector described in step S2 includes copper foil, aluminum foil, carbon-coated copper foil, carbon-coated aluminum foil or carbon paper.

6. The method for preparing a thin film according to claim 1, characterized in that: The temperature treatment method described in step S4 includes one or a combination of two or more of direct heating, ultraviolet irradiation, infrared irradiation, and microwave heating.

7. A film, characterized in that: A film prepared by the method for preparing a film as described in any one of claims 1 to 6.

8. An energy storage device, comprising a positive electrode, a negative electrode and a separator, characterized in that: The present invention is prepared by using the thin film according to claim 7 as a positive electrode, or / and a negative electrode, or / and a separator.